Health system bottlenecks hindering provision of supportive and dignified maternity care in public health facilities - Waqas Hameed; Bushra Khan; Sameen Siddiqi; Muhammad Asim; Bilal Iqbal Avan (Public Library of Science (PLoS), 2022)
Mistreatment with women during childbirth is prevalent in many in low- and middle-income countries. There is dearth of evidence that informs development of health system interventions to promote supportive and respectful maternity care in facility-based settings. We examined health systems bottlenecks that impedes provision of supportive and respectful maternity care in secondary-level public healthcare system of Pakistan. Using a qualitative exploratory design, forty in-depth interviews conducted with maternity care staff of six public health facilities in southern Pakistan. Development of interview guide and data analyses were guided by the WHO's six health system building blocks. A combination of inductive and deductive approach was used for data analyses. Our study identified range of bottlenecks impeding provision of RMC. In terms of leadership/governance, there was lack of institutional guidelines, supervision and monitoring, and patient feedback mechanism. No systematic mechanism existed to screen and record patient psychosocial needs. Health workforce lacked training opportunities on RMC that resulted in limited knowledge and skills; there were also concerns about lack of recognition from leadership for good performers, and poor relationship and coordination between clinical and non-clinical staff. Regarding the domain of service delivery, we found that patients were perceived as un-cooperative, non-RMC manifestations were acceptable and normalized under certain conditions, and restrictive policies for active engagement of companions. Finally, lack of cleanliness, curtains for privacy, seating arrangement for companion were the identified issues infrastructural issues. A service-delivery intervention package is needed that effectively uses all six components of the health system: from investments in capacity building of maternity teams to creating a conducive facility environment via proper governance and accountability mechanisms. Such interventions should not only focus on provision of maternity care in a respectful and dignified manner, but also ensure that care is responsive to the psychosocial needs of pregnant women without any discrimination.